THE RELATIONSHIP BETWEEN SMOKING BEHAVIOR AND SELF-CONFIDENCE IN ADOLESCENT VOCATIONAL SCHOOL STUDENTS - Ade Fitriani; Dadi Hamdani; Elis Roslianti; Henri Setiawan; Andan Firmansyah (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Smoking behavior is a function of both the environment and the individual, which means that smoking behavior is not only caused by internal factors, but also by environmental factors. Furthermore, smoking behavior in adolescents is a symbolic behavior that represents leadership maturity and opposite-sex attractiveness. After China and India, Indonesia has the third-highest number of smokers in the world. When a boy has a positive relationship with adults that makes him feel understood, valued, and wanted, and when he feels supported so that he excels in school, he becomes competent and confident. Similarly, a girl learns to socialize and face the future with confidence and courage as a result of her various attachments. The goal of this study is to determine whether there is a correlation between smoking and self-confidence among vocational students. This research used a cross-sectional, observational, analytic methodology. 13 individuals (19.1%) had a positive smoking behavior status with strong self-confidence, while 36 individuals (52.9%) had a negative smoking behavior status. Based on the chi-square test, the p-value was found to be 0.001: 0.05, indicating a link between smoking behavior and self-confidence. The majority of teenage males' smoking behavior is bad, and the majority of male self-confidence falls into the category of low self-esteem. There is a correlation between vocational students' smoking behavior and their confidence.